Short Communication: The potential of soil microbes in the three kerangas forest ecosystems on Belitung Island, Indonesia - DINA OKTAVIA; SANTI DWI PRATIWI; DESTY PRATIWI; NADIA NURANIYA KAMALUDIN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Oktavia D, Pratiwi SD, Pratiwi D, Kamaludin NN. 2023. Short Communication: The potential of soil microbes in the three kerangas forest ecosystems on Belitung Island, Indonesia. Biodiversitas 24: 1895-1899. The biogeochemical cycles on Earth are governed by living creatures, therefore the composition and activity of microbial communities are important ecological issues. In this study, we investigated the abundance of soil microbes randomly existing from the three types of kerangas forest ecosystems (Bukit Peramun, Cendil Kerangas Forest, and Gunung Lumut) in Belitung Island which belongs to the Geosites of Belitong UNESCO Global Geopark. In comparison to the Bukit Peramun and Hutan Cendil habitats, the populations of bacteria and fungus in the Gunung Lumut were greater at 3.11 x 1010 and 1.14 x 105 cfu g-1, respectively. In Gunung Lumut, there was a comparatively high population of soil bacteria. Gunung Lumut is a site where a variety of mosses have taken over and are overpowered by the terrain due to its high humidity and weathered rocks. Generally, under various conditions, a specific function is more likely to be carried out by soils with higher microbial populations. Understanding soil health and agricultural productivity depends on an understanding of the presence of soil bacteria in various types of kerangas forests. Our study aids the Geosites of the Belitong UNESCO World Geopark in ensuring a long-term sustainable ecosystem.